Cybersecurity framework for SMEs in Peru based on ISO/IEC 27001 and CSF NIST controls - Angelo Edu, Munoz Luyo (2023)
Due to the global pandemic that was experienced in 2020, the Small and Medium Enterprises (SMEs) sector in Peru chose to store all their information in cloud services. However, a 2021 Kaspersky study indicates that SMBs have few resources to implement security solutions to protect their information. For this reason, this article proposes a cybersecurity framework composed of controls from ISO/IEC 27001 and the Cybersecurity Framework (CSF) of the National Institute of Standards and Technology (NIST) to mitigate cyber-threats against SMEs in Peru. The framework consists of 7 steps having as reference the Deming cycle (PDCA). For the implementation of the composite framework, we worked with 12 domains and 40 controls for a Peruvian SME in the technology sector. The results showed an increase in cybersecurity of 40 %, after applying the 40 controls, improving its level of maturity from the 'insufficient' state to a 'mature' state, according to the assessment given.